Keberadaan jentik nyamuk aedes aegypti dengan kejadian demam berdarah dengue (DBD) - Irwan Ashari; Taufik Kurrohman; Matheus Aba; Endang Surjati; Efendi Efendi (Holistik Jurnal Kesehatan, 2023)
Background: The incidence of dengue fever in the City of Bandung is still a problem that must be resolved immediately. Efforts to eradicate mosquito nests are one of the most effective ways to reduce disease transmission. Eradication can be carried out from mosquitoes still in the form of larvae.Purpose: To determine the relationship between the presence of aedes aegypti mosquito larvae with the incidence of dengue haemorrhagic fever.Method: A cross-sectional study was conducted in the working area of Puter Health Centre. The research sample was taken using the stratified random sampling technique, which was 63 respondents. The instrument in this study was to use a checklist sheet using the observation method. Data analysis using chi-square test.Results: Most of the houses observed did not have mosquito larvae, of 63.5 per cent, and most did not suffer from dengue haemorrhagic fever, which was 82.5 per cent. There is a relationship between the presence of mosquito larvae and the incidence of dengue haemorrhagic fever.Conclusion: People who live in homes with mosquito larvae are 6.5 times more likely to suffer from dengue haemorrhagic fever compared to people who live in homes where there are no mosquito larvae.Suggestion: To the Public Health Centre to optimize larva monitor cadres to carry out monitoring every week at people's homes.Keywords: Dengue hemorrhagic fever; Larvae; Aedes aegyptiPendahuluan: Kejadian demam berdarah di Kota Bandung masih menjadi permasalahan yang harus segera diselesaikan. Upaya pemberantasan sarang nyamuk adalah salah satu cara yang cukup efektif dalam menekan penularan penyakit. Pemberantasan dapat dilakukan dari nyamuk masih dalam bentuk larva atau jentik.Tujuan: Untuk mengetahui keberadaan jentik nyamuk aedes aegypti dengan kejadian demam berdarah dengue.Metode: Penelitian cross sectional dilakukan di wilayah kerja Puskesmas Puter. Sampel penelitian diambil dengan teknik stratified random sampling yaitu sebanyak 63 responden. Instrumen dalam penelitian ini yaitu menggunakan lembar checklist dengan menggunakan metode observasi. Analisis data menggunakan uji chi square.Hasil: Sebagian besar rumah yang di observasi tidak terdapat jentik nyamuk yaitu 63,5 persen, dan sebagian besar tidak menderita demam berdarah dengue yaitu 82,5 persen. Ada hubungan antara keberadaan jentik nyamuk dengan kejadian demam berdarah dengue.Simpulan: Orang yang tinggal di rumah yang terdapat jentik nyamuk berpeluang 6,5 kali menderita demam berdarah dengue dibandingkan dengan orang yang tinggal di rumah yang tidak terdapat jentik nyamuk.Saran: Kepada pihak Puskesmas agar mengoptimalkan kader jumantik untuk melakukan monitoring setiap minggu ke rumah-rumah masyarakat.